Physical Education: “a stranger animal than the platypus” (Research, Society and Development, 2021)
The present essay, with a reflective character, is constituted from the objective of elucubating about the field of Physical Education (EF) in Brazil through an analogy with the platypus. The justification for this aim is that there are “metaphorical similarities” between the platypus and EF. With the intention of developing this metaphor, in the first topic, we present some “approximations” between the platypus and EF. In the second topic, we tried to discuss and rutile some possibilities to think about PE, especially with regard to the epistemological plurality of the field, as a possible alternative for (relative) unity among the different Physical Educations. We bet on the dialogical disposition for the plurality of the field of Brazilian EF, seeking recognition for the singularities that constitute it (to the despair of the catalogers on duty).